2017
DOI: 10.1007/s40615-017-0346-0
|View full text |Cite
|
Sign up to set email alerts
|

Are Ethnic Disparities in HbA1c Levels Explained by Mental Wellbeing? Analysis of Population-Based Data from the Health Survey for England

Abstract: AimsIt is unclear how ethnic differences in HbA1c levels are affected by individual variations in mental wellbeing. Thus, the aim of this study was to assess the extent to which HbA1c disparities between Caucasian and South Asian adults are mediated by various aspects of positive psychological functioning.MethodsData from the 2014 Health Survey for England was analysed using bootstrapping methods. A total of 3894 UK residents with HbA1c data were eligible to participate. Mental wellbeing was assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Our study found a small ( B = −0.296) but non-significant effect of ethnicity on HbA1c, perhaps in part attributable to the lack of diversity in our sample. A recent investigation of HbA1c levels in Caucasian and South Asian adults taking part in the Health Survey for England showed that ethnic difference in HbA1c was mediated by positive wellbeing (Umeh, 2018 ). Other previous work suggests that ethnic differences in diabetes incidence are not purely attributable to income disparities, with factors such as differences in health behaviors including diet, obesity, smoking, and physical activity (Gujral et al ., 2013 ) also being relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a small ( B = −0.296) but non-significant effect of ethnicity on HbA1c, perhaps in part attributable to the lack of diversity in our sample. A recent investigation of HbA1c levels in Caucasian and South Asian adults taking part in the Health Survey for England showed that ethnic difference in HbA1c was mediated by positive wellbeing (Umeh, 2018 ). Other previous work suggests that ethnic differences in diabetes incidence are not purely attributable to income disparities, with factors such as differences in health behaviors including diet, obesity, smoking, and physical activity (Gujral et al ., 2013 ) also being relevant.…”
Section: Discussionmentioning
confidence: 99%